Feeling Free and Having an Authentic Inner Compass as Important Aspects of the Need for Autonomy in Emerging Adults’ Interactions With Their Mothers - Avi Assor; Rinat Cohen; Ohad Ezra; Shi Yu (Frontiers in Psychology, 2021)
Based on past theorizing and research, we posited that there are two kinds of specific experiences that contribute to the satisfaction of the general need for autonomy in emerging adults, as reflected in volitional, self-endorsed, actions. These experiences are: (1) feeling free, and (2) having a valid authentic inner compass (AIC). In the first study testing this hypothesis, college students in Israel (n = 163, mean age = 21.33), and in China (n = 72, mean age = 23.67) completed measures assessing experiences of freedom and having a valid AIC during contacts with mothers, extent of volitional contacts with mothers, and vitality during contacts with mothers. Confirmatory factor analyses and invariance analysis supported the validity of the measures, and their equivalence across cultures. In the Israeli sample, students also completed a measure assessing the extent to which the sense of having a valid AIC during contacts with one’s mother is based on intrinsic aspirations and goals. As expected, across cultures, participants distinguished between experiences of (a) having a valid AIC, and (b) feeling free. The findings also suggest that experiences of freedom and of having a valid AIC during contacts with mothers are associated with extent of volitional contacts with mother, and subsequent vitality during these contacts. Also as expected, experiencing a valid AIC during contacts with mother was associated with volitional contacts with her and subsequent vitality - only when the AIC was based on intrinsic aspirations. The results suggest that in assessing people’s sense of AIC, it is important to consider the content of the aspirations and goals on which this sense is based. The findings are consistent with the view that feeling free, and having a valid AIC are two specific autonomy experiences which promote a more global experience of need autonomy satisfaction, as indicated by feelings of volitional and self-endorsed action.